A new realization method for multidimensional GIC digital filters - Eswaran, C.; Rameshwaran, K. (2002)
A simple and straightforward procedure for the realization of multidimensional digital filters which are based on the concept of generalized immittance converter is presented in this brief. It is known that these digital filters possess many salient features such as low noise, low sensitivity, absence of limit cycles and capability of realizing multiple transfer functions. Unlike the other known methods, which use analog transfer function as the basis, the method proposed in this paper uses the discrete transfer function directly for realization. It is shown that the required details of the resulting filter structure, namely, the organization of the different adaptors and the values of the multiplier constants can be obtained directly from the specified discrete transfer function.